Persepsi Masyarakat terhadap Dampak dan Penyebab Banjir serta Upaya Penanggulangannya: Studi Kasus Perumahan Haji Saleh, Samarinda: Community Perceptions of Flood Impacts, Causes, and Mitigation Efforts: A Case Study of Haji Saleh Housing Complex, Samarinda - Betty Pelegia Sitompul; Shalehudin Denny Maruf; Martha Ekawati Siahaya; Fachruddin Azwari; Wardatul Hidayah (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2026)
Flooding has become one of the recurring environmental problems affecting residential areas in Samarinda City, with significant repercussions across multiple dimensions of community life. This study was designed to examine how residents perceive the impacts, triggering factors, and flood mitigation measures undertaken in the Haji Saleh Housing Complex, Loa Janan Ilir Subdistrict. A descriptive quantitative method was employed using a Likert-scale questionnaire (1–5). A total of 40 respondents were selected through purposive sampling, with an age criterion of 15–64 years. Data were analyzed using mean values. The findings reveal that all measured indicators fell within the high to very high categories, yielding an overall mean score of 4.42. Respondents identified heavy rainfall as the primary triggering factor of flooding (mean 4.68), while inadequate drainage capacity also contributed significantly (mean 4.65). The most dominant impacts were property damage (4.60) and mobility disruption (4.53). Meanwhile, community-based flood mitigation efforts were categorized as high. These results indicate that residents possess a strong flood risk perception, underscoring the need for strengthened collaboration between government and community in sustaining mitigation efforts and improving drainage infrastructure on an ongoing basis.